2015
DOI: 10.1002/ijc.29424
|View full text |Cite
|
Sign up to set email alerts
|

High‐risk HPV testing in the management of atypical glandular cells: A systematic review and meta‐analysis

Abstract: Whereas the utility of high-risk HPV (hrHPV) testing is widely accepted in triage of women with atypical squamous lesions, its role in managing atypical glandular cells (AGC) is not fully elucidated. A systematic review and meta-analysis were performed to evaluate the accuracy of hrHPV testing in the management of women with AGC to detect underlying high-grade intraepithelial neoplasia or worse, and adenocarcinoma in situ or worse (AIS1). Additionally, the diagnosis of extra-cervical cancer was considered as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…Pirog et al [21] examined HPV in cervical AC by PCR methodology in 682 cases and found that "cervical AC, usual type" had the highest proportion of HPV-positive cases (71.8%), with HPV positivity for the rarer subtypes as follows: endometrioid (27.3%), serous (25%), and clear cell (20%) [21]. Ronco et al [22] found a clinically significant gain in detection of glandular lesions when adding HPV testing to cytology, while Verdoodt et al [23] in a meta-analysis found that reflex HPV testing was generally unnecessary as the pretest probability of finding a clinically relevant lesion was sufficient for the next clinical decisions [22,23]. In the present study we did not have HPV testing data available for most cases as in 2011 cotesting was less common than in current practice.…”
Section: Discussionmentioning
confidence: 99%
“…Pirog et al [21] examined HPV in cervical AC by PCR methodology in 682 cases and found that "cervical AC, usual type" had the highest proportion of HPV-positive cases (71.8%), with HPV positivity for the rarer subtypes as follows: endometrioid (27.3%), serous (25%), and clear cell (20%) [21]. Ronco et al [22] found a clinically significant gain in detection of glandular lesions when adding HPV testing to cytology, while Verdoodt et al [23] in a meta-analysis found that reflex HPV testing was generally unnecessary as the pretest probability of finding a clinically relevant lesion was sufficient for the next clinical decisions [22,23]. In the present study we did not have HPV testing data available for most cases as in 2011 cotesting was less common than in current practice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genotyping of hrHPVpositive ASC-US revealed a type-dependent, 10-fold range in 3-year risk of CIN3+, which suggests that genotyping of HPV might be useful for risk stratification of ASC-US [19]. A meta-analysis showed that hrHPV DNA test results, when combined with age, distinguish the risk for AGC lesions with cervical versus noncervical cytology, which improves the diagnostic process [17]. However, few studies have evaluated hrHPV genotype distribution in women with AGC.…”
Section: Discussionmentioning
confidence: 99%
“…Verdoodt et al [17] conducted a meta-analysis to examine the accuracy of hrHPV testing for identifying or excluding (pre)cancerous lesions of the uterine cervix and reported that 19.8% of women with AGC were classified as CIN2+/AIS+. The prevalence of CIN2+/AIS+ was 22-48% in previous studies examining 50-100 cases of AGC, whereas 1 Japanese study reported that 87.5% of women diagnosed with AGC were classified as CIN2+/AIS+ [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Bethesda System recommends reporting of EMC, the significance of these cells in detecting endometrial adenocarcinoma remains controversial [2,3,4,5,6,7]. While additional testing for high-risk human papilloma virus helps in detecting high-grade cervical squamous and glandular lesions, it cannot rule out an elevated risk of extracervical malignancy [8]. We performed a similar study, in which we investigated the clinical significance of ‘out-of-phase' normal EMC (nEMC), atypical EMC (aEMC) and aEMC favoring neoplasia/endometrial carcinoma in Pap smears from women attending an organized cervical cancer screening program.…”
Section: Tablementioning
confidence: 99%